Why enough is never enough: the societal determinants of river basin closure - Molle, Francois (2008)
Manifestations of water scarcity are increasingly frequent, even in regions with temperate climates and endowed with good water resources. This paper argues that several 'bad good reasons' and mechanisms are at work to generate 'overbuilt basins', whereby the development of infrastructural resources invariably tends to outstrip available resources. Eight main drivers of basin overbuilding are proposed and discussed. Despite its crucial importance and ubiquity, this phenomenon is often overlooked. Unpacking the reasons why 'enough is never enough', i.e. why water resources become over-committed and river basins overbuilt, is critical if these mechanisms are to be countered.